A novel educational intervention targeting melanoma risk and prevention knowledge among children with a familial risk for melanoma. Issue 3 (March 2018) - Wu, Yelena P.; Nagelhout, Elizabeth; Aspinwall, Lisa G.; Boucher, Kenneth M.; Parsons, Bridget G.; Kohlmann, Wendy; Kaphingst, Kimberly A.; Homburger, Sheila; Perkins, Ryan D.; Grossman, Douglas; Harding, Garrett; Leachman, Sancy A.
Highlights: Children at risk for melanoma benefitted from a preventive educational program. The program was innovative in its presentation of mechanisms mitigating melanoma risk. The program increased knowledge and engagement in melanoma preventive behaviors. Abstract: Objective: To examine the acceptability of and preliminary effects associated with a novel educational intervention for children at elevated risk for melanoma. The intervention incorporated information on mechanisms through which melanoma preventive behaviors mitigate risk for melanoma and was delivered to parents and children concurrently. Methods: Twenty-two parents (with a personal history of melanoma or spouse with a history of melanoma) and 33 children (mean age 11.8 years) were asked to complete questionnaires immediately prior to and after an educational session and at a one-month follow-up. Results: Both parents and children endorsed that the educational materials were acceptable. Knowledge about melanoma risk and preventive and screening behaviors increased significantly. Children's perceived risk for melanoma increased significantly, while parents' perceptions of children's risk started at a higher level and remained constant. There were significant increases in reported engagement in sun protective behaviors. Conclusion: The educational intervention shows promise in terms of its acceptability and effects on participant knowledge, perceived risk, and engagement in melanoma preventive behaviors. Practice implication: Children at elevated risk for melanoma and their parents may benefit from receiving educational information on their disease risk and strategies for prevention and screening.